Characterization and technological functions of different lactic acid bacteria from traditionally produced Kırklareli white brined cheese during the ripening period - Çetin, Bayram; Usal, Merve; Aloğlu, Hatice Şanlıdere; Busch, Annemarie; Dertli, Enes; Abdulmawjood, Amir (Folia microbiologica, 2024)
In the present study, the evolution of the physicochemical and microbiological characteristics of lactic acid bacteria (LAB) in traditional Kırklareli white brined cheese collected from 14 different cheese manufacturing facilities were investigated on different days of the 90-day ripening period. The obtained LAB within the species Lactococcus (Lc.) lactis, Latilactobacillus (Lt.) curvatus, Lactobacillus (Lb.) casei and Lb. plantarum, Enterococcus (E.) durans, E. faecium, E. faecalis, Streptococcus macedonicus, and Weissella paramesenteroides were characterized in terms of their influence on technological properties and their potential as starter cultures for traditional white brined cheese production. The results of the microbiological and physicochemical investigations showed that a few selected isolates of Lc. lactis, Lb. casei, and Lb. plantarum had certain functions as starter germs. Moderate acidification capacity, antibacterial activity and proteolytic activity, which are characteristic of their use as starter lactic acid bacteria, were found. Importantly, antibiotic resistance among selected Lc. lactis, Lb. casei, and Lb. plantarum isolates was extremely low, whereas some of these isolates demonstrated antibacterial activity against major foodborne pathogenic bacteria. Based on the results obtained in this study, selected Lc. and Lb. isolates can also be considered as starter culture in traditional cheese production.
Keywords: Food Microbiology; Cheese; Lactobacillales; Fermentation; sýr; Anti-Bacterial Agents; potravinářská mikrobiologie; fermentace; antibakteriální látky